2012
DOI: 10.1097/prs.0b013e31823ae86c
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Increases the Risk of Microvascular Flap Complications in Patients Undergoing Microvascular Breast Reconstruction

Abstract: Background Tamoxifen citrate (tamoxifen) has been associated with increased rates of thromboembolic events, which have prompted concerns that tamoxifen may increase the risk of complications after microvascular breast reconstruction. Some centers have implemented protocols to temporarily stop tamoxifen before microvascular breast reconstruction. We sought to determine whether this practice is warranted. Methods We retrospectively compared rates of microvascular flap complications and pulmonary emboli between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 12 publications
1
23
2
Order By: Relevance
“…7,8 The available options include tamoxifen, aromatase inhibitors, and fulvestrant. [9][10][11][12][13][14][15] Furthermore, approximately 15 to 20 percent of breast cancers have amplification of the human epidermal growth factor receptor-2 (HER-2) gene, which plays a role in epithelial cell mitosis, invasion, and antiapoptosis. 16,17 Trastuzumab (Herceptin; Genentech, South San Francisco, Calif.) is a fully humanized monoclonal antibody developed to target the extracellular domain of HER-2 and is widely used in patients with HER-2-positive breast cancer.…”
mentioning
confidence: 99%
“…7,8 The available options include tamoxifen, aromatase inhibitors, and fulvestrant. [9][10][11][12][13][14][15] Furthermore, approximately 15 to 20 percent of breast cancers have amplification of the human epidermal growth factor receptor-2 (HER-2) gene, which plays a role in epithelial cell mitosis, invasion, and antiapoptosis. 16,17 Trastuzumab (Herceptin; Genentech, South San Francisco, Calif.) is a fully humanized monoclonal antibody developed to target the extracellular domain of HER-2 and is widely used in patients with HER-2-positive breast cancer.…”
mentioning
confidence: 99%
“…The study by Mirzabeigi et al 8 suggests that, at a minimum, tamoxifen therapy can continue up to at least 2 weeks prior to reconstruction without affecting microvascular flap complications. Kelley et al, 7 however, stated that tamoxifen may need to be held up to 1 month prior to surgery. As previously described, the inclusion of non-abdominally based flaps and higher irradiation rates in the tamoxifen group may have contributed to the increased complication rates that were observed by the authors.…”
Section: Discussionmentioning
confidence: 97%
“…Recent retrospective studies comparing stopping tamoxifen at different timepoints prior to reconstruction have provided conflicting conclusions. Kelley et al 7 reported an increased in flap complications by 1.7 times in patients receiving tamoxifen up to 1 month prior to reconstruction. On the other hand, a recent study by Mirzabeigi et al 8 showed no increase in complications in patients who stopped tamoxifen 2 weeks prior to abdominally based microvascular breast reconstruction.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The available options include tamoxifen, aromatase inhibitors, and fulvestrant (11)(12)(13)(14)(15)(16). A prospective randomized trial performed in 1995, comparing modified radical mastectomy to hormone therapy followed by modified radical mastectomy found that there was no significant difference in the risk of complications and that immediate breast reconstruction was not an independent predictor of complications (17).…”
Section: Hormonal Therapymentioning
confidence: 99%